1993
DOI: 10.1056/nejm199305203282004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Consumption and the Risk of Coronary Heart Disease in Men

Abstract: These data do not prove a causal relation, but they provide evidence of an association between a high intake of vitamin E and a lower risk of coronary heart disease in men. Public policy recommendations with regard to the use of vitamin E supplements should await the results of additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
856
2
23

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,136 publications
(911 citation statements)
references
References 43 publications
30
856
2
23
Order By: Relevance
“…In the Nurses' Health Study consumption of vitamin E supplements for > 2 years was found to be associated with a 41% lower relative risk of major coronary disease (58) . Similar results were obtained in an observational study in male health professionals, for whom there was a 37% lower relative risk of CHD in those who took vitamin E supplements in doses of ‡ 100 mg daily for > 2 years (59) .…”
Section: Vitamin Esupporting
confidence: 83%
“…In the Nurses' Health Study consumption of vitamin E supplements for > 2 years was found to be associated with a 41% lower relative risk of major coronary disease (58) . Similar results were obtained in an observational study in male health professionals, for whom there was a 37% lower relative risk of CHD in those who took vitamin E supplements in doses of ‡ 100 mg daily for > 2 years (59) .…”
Section: Vitamin Esupporting
confidence: 83%
“…Accordingly, a study of the Harvard School of Public Health in over 120,000 persons in health-related professions shows that those that ingest high levels of antioxidants reduce their risk of suffering coronary disease up to 40% (32). Likewise, according to the Cambridge Heart Antioxidant Study (33), administration of a daily dose of 400-800 I.U.…”
Section: Resultsmentioning
confidence: 99%
“…This may be through the inhibition of LDL oxidation and reduced inflammatory response (Abbey, 1995;Hercberg et al, 1998;Kromhout, 2001), and mechanisms may include modulation of cellular signalling pathways (Pryor, 2000;Neuzil et al, 2001). The most notable positive findings on vitamin E come from two large epidemiological studies in the United States, where subjects with the highest vitamin E intake had a 30-40% reduction in CVD risk (Rimm et al, 1993;Stampfer et al, 1993). This association was mainly attributed to high vitamin E consumption from nutrient supplements; however, other observational studies have demonstrated protective effects from food-derived vitamin E alone (Knekt et al, 1994;Kushi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%